Quality of life prior and in the course of the COVID-19 pandemic : a nationwide cross-sectional study with Brazilian dietitians - Matos, Raquel Adjafre da Costa (2021)
This nationwide cross-sectional research aimed to evaluate Brazilian dietitians’ quality of life prior and in the course of the COVID-19 pandemic, using a previously validated self-administered instrument WHO-QOL-BREF in Brazilian-Portuguese. Other sociodemographic variables and three questions about the COVID-19 pandemic period were included, and the instrument was applied using GoogleForms®. Paired T-test, Chi-squared test, and Analysis of Variance were used for statistical analysis. A total of 1290 Brazilian dietitians replied the instrument. QoL before SARS-COV-2 (3.83±0.59) was statistically different from during the pandemic (3.36±0.66). Comparing prior and in course of the COVID-19 pandemic, all variables and domains presented statistical diferences (better before the pandemic period). The second domain (psychological health) was the most affected among Brazilian dietitians. The Sars-Cov-2 pandemic was associated with a negative impact on QoL of Brazilian dietitians, health professionals that faced changes in different areas of their lives.